A Novel Network Pharmacology Strategy Based on the Universal Effectiveness-Common Mechanism of Medical Herbs Uncovers Therapeutic Targets in Traumatic Brain Injury - Yu Z; Ding R; Yan Q; Cheng M; Li T; Zheng F; Zhu L; Wang Y; Tang T; Hu E (Drug Design, Development and Therapy, 2024)
Zhe Yu,1– 3 Ruoqi Ding,1– 3 Qiuju Yan,1– 3 Menghan Cheng,1– 3 Teng Li,1– 4 Fei Zheng,5 Lin Zhu,1– 4 Yang Wang,1– 4 Tao Tang,1– 4 En Hu1– 4 1Institute of Integrative Medicine, Department of Integrated Traditional Chinese and Western Medicine, Xiangya Hospital, Central South University, Changsha, 410008, People’s Republic of China; 2NATCM Key Laboratory of TCM Gan, Xiangya Hospital, Central South University, Changsha, 410008, People’s Republic of China; 3Center for Interdisciplinary Research in Traditional Chinese Medicine, Xiangya Hospital, Central South University, Changsha, 410008, People’s Republic of China; 4Xiangya Hospital, Central South University, Nanchang, Jiangxi, 330004, People’s Republic of China; 5The College of Integrated Traditional Chinese and Western Medicine, Hunan University of Chinese Medicine, Changsha, 410008, People’s Republic of ChinaCorrespondence: En Hu; Ruoqi Ding, Integrative Medicine, Department of Integrated Traditional Chinese and Western Medicine, Xiangya Hospital, Central South University, Changsha, 410008, People’s Republic of China, Email znxyhe@csu.edu.cn; ruoqi_ding@outlook.comPurpose: Many herbs can promote neurological recovery following traumatic brain injury (TBI). There must lie a shared mechanism behind the common effectiveness. We aimed to explore the key therapeutic targets for TBI based on the common effectiveness of the medicinal plants.Material and methods: The TBI-effective herbs were retrieved from the literature as imputes of network pharmacology. Then, the active ingredients in at least two herbs were screened out as common components. The hub targets of all active compounds were identified through Cytohubba. Next, AutoDock vina was used to rank the common compound-hub target interactions by molecular docking. A highly scored compound-target pair was selected for in vivo validation.Results: We enrolled sixteen TBI-effective medicinal herbs and screened out twenty-one common compounds, such as luteolin. Ten hub targets were recognized according to the topology of the protein-protein interaction network of targets, including epidermal growth factor receptor (EGFR). Molecular docking analysis suggested that luteolin could bind strongly to the active pocket of EGFR. Administration of luteolin or the selective EGFR inhibitor AZD3759 to TBI mice promoted the recovery of body weight and neurological function, reduced astrocyte activation and EGFR expression, decreased chondroitin sulfate proteoglycans deposition, and upregulated GAP43 levels in the cortex. The effects were similar to those when treated with the selective EGFR inhibitor.Conclusion: The common effectiveness-based, common target screening strategy suggests that inhibition of EGFR can be an effective therapy for TBI. This strategy can be applied to discover core targets and therapeutic compounds in other diseases.Keywords: traditional Chinese medicine, medicinal plants, luteolin, AZD3759, epidermal growth factor receptor, astrocyte